Bonobos and chimpanzees preferentially attend to familiar members of the dominant sex. (July 2021) - Lewis, Laura S.; Kano, Fumihiro; Stevens, Jeroen M.G.; DuBois, Jamie G.; Call, Josep; Krupenye, Christopher
Abstract : Social animals must carefully track consequential events and opportunities for social learning. However, the competing demands of the social world produce trade-offs in social attention, defined as directed visual attention towards conspecifics. A key question is how socioecology shapes these biases in social attention over evolution and development. Chimpanzees, Pan troglodytes, and bonobos, Pan paniscus, provide ideal models for addressing this question because they have large communities with fission–fusion grouping, divergent sex-based dominance hierarchies and occasional intergroup encounters. Using noninvasive eye-tracking measures, we recorded captive apes' attention to side-by-side images of familiar and unfamiliar conspecifics of the same sex. We tested four competing hypotheses about the influence of taxonomically widespread socioecological pressures on social attention, including intergroup conflict, dominance, dispersal and mating competition. Both species preferentially attended to familiar over unfamiliar conspecifics when viewing the sex that typically occupies the highest ranks in the group: females for bonobos, and males for chimpanzees. However, they did not demonstrate attentional biases between familiar and unfamiliar members of the subordinate sex. Findings were consistent across species despite differences in which sex tends to be more dominant. These results suggest that sex-based dominance patterns guide social attention across Pan . Our findings reveal how socioecological pressures shape social attention in apes and likely contribute to the evolution of social cognition across primates. Highlights: Bonobos and chimpanzees discriminate faces of familiar and unfamiliar conspecifics. Great apes devote greater social attention to familiar members of the dominant sex. Species differences in male vs female dominance shape patterns of social attention. Both selective pressures and socialization likely drive patterns of social attention.